Conversations Amidst Computing: A Study of Interruptions and Recovery of Task Activity - Iqbal, Shamsi; Horvitz, Eric (2007)
We present results from a field study investigating the influence of conversations on the multitasking behavior of computer users. We report on several findings, including the timing of the resumption of tasks following conversational interruptions and on the nature and rate of computing activities that are performed concurrently with conversation.